Interpersonal facilitation : comparison of its effects on performance ratings for managerial and non-managerial jobs. - Ng, Ann Ee. (2008)
This project extends previous research on contextual performance, specifically interpersonal facilitation and its effects on performance to managerial and non-managerial jobs.